Understanding resilience among migrant women in a humanitarian reception center: a qualitative study - Jiménez-Lasserrotte, María del Mar; Sánchez-Ojeda, María Angustias; Vázquez-González, Gloria; Ruiz-Fernández, María Dolores; Peña-Rodríguez, Azahara; Fernández-Medina, Isabel María; Granero-Molina, José (Frontiers in Public Health, 2024)
Background The European Union receives thousands of irregular migrants and refugees annually. Irregular migrant women are admitted to Humanitarian Reception Centers. These migrants face multiple adversities on their migration journey, and resilience is key to coping with process. The aim of this study was to describe and understand irregular migrant women’s experience of resilience when living in humanitarian reception centers. Methods Descriptive qualitative study. In-depth interviews and a focus group were carried out with 21 migrant women from different African countries, with an average age of 31.8 years. Thematic analysis was used to analyze the qualitative data using ATLAS.ti computer software. Results Three main themes emerged: (1) Irregular migrant women in transit: extreme vulnerability. (2) Migration support networks. (3) Promoting irregular migrant women’s resilience. Conclusion The harshness of the migration process tests the resilience of irregular migrant women, who are a vulnerable group at high risk of social exclusion. Their time in humanitarian reception centers is significant in their process of developing resilient behaviors. The multidisciplinary resources of the humanitarian reception center help the irregular migrant women in their personal development.